The Emperor, the Jews, and the anatomy of Empire - Mark Humphries (Hermathena, 2022)
In 398 CE, the western Roman emperor Honorius issued a law condemning attempts by Jewish town councillors in southern Italy to seek exemptions from compulsory public services. While this law is usually read for the light it sheds on the legal situation of Jews in the Christian Roman empire, it is argued here that the ruling is also concerned with another issue. It was issued three years after the division of the Roman empire into two halves, East and West, each with its own administrative structures, and with its emperor issuing laws for territories under his jurisdiction. Honorius notes that Italian Jews claimed exemptions in accordance with recent eastern legislation but rejects its validity for the West. This indicates how tensions between East and West caused difficulties for Italian Jews who, because of their pan-Mediterranean connections, did not fit easily into the empire’s administrative frameworks.